Masculinities, Femininities and Work – The Horizontal Gender Segregation in the Danish Labour Market - Bloksgaard, Lotte (Nordic Journal of Working Life Studies, 2011)
Most job functions, tasks and professions are gendered as either ‘masculine’ or ‘feminine’. On the basis of two empirical studies of women in ‘men’s jobs’ and men in ‘women’s jobs’ the article shows how societal ideas about and relations between gender and work affect the way in which individual women and men develop their identities and hereby influence women’s and men’s work orientations and working life. Thus, the article provides a greater understanding of the gendering processes which contribute to the creation of gender segregation in the Danish labour market.